Design and evaluation of sustained release spherical agglomerates of Fluvastatin sodium by crystallo-co-agglomeration - Dushyant Shaha, Kishorkumar Sorathiab (Journal of Applied Pharmaceutical Science, 2017)
Prime objective of present study was to design and evaluate ready to compress sustained release spherical agglomerates of Fluvastatin sodium. Crystallo-co-agglomeration technique of spherical crystallization utilizing acetone-acetonitrile system was used to prepare spherical agglomerates of drug in presence of Eudragit RS100 and RL100 as release retardant polymers. Prepared agglomerates were subjected for evaluation of flow, packing, mechanical, compaction properties as well as in-vitro dissolution study. Morphology of spherical agglomerates was evaluated by SEM and drug-polymer compatibility was carried out by DSC, FTIR and XRD. Matrix beads were generated having uniform dispersion of drug with enhanced flow, packing, compaction and mechanical properties which can be attributed to spherical shape of agglomerates as revealed in SEM photomicrographs. Higher crushing strength of agglomerates was indication of good mechanical strength. Improved compressibility of agglomerates was indicated by lower values of σ0, improved tensile strength and reduced elastic recovery. DSC, FTIR and XRD showed that drug did not undergo structural or polymorphic alterations in presence of polymers. In-vitro dissolution study suggested utilization of process for sustained release of fluvastatin sodium for sufficiently prolonged period of time depending on polymer concentration. Thus, crystallo-co-agglomeration method can be successfully utilized for development of directly compressible sustained release agglomerates.
Keywords: Crystallo-co-agglomeration,direct compression,Fluvastatin sodium, spherical crystallization, sustained release.